2017
DOI: 10.1530/eje-17-0071
|View full text |Cite
|
Sign up to set email alerts
|

MR spectroscopy of hepatic fat and adiponectin and leptin levels during testosterone therapy in type 2 diabetes: a randomized, double-blinded, placebo-controlled trial

Abstract: The effects of TRT on cardiovascular risk markers were ambiguous. We observed potentially harmful changes in cardiovascular risk parameters, markedly reduced subcutaneous fat and unchanged ectopic fat during TRT and a reduction in adiponectin levels. On the other hand, the decrease in leptin and leptin:adiponectin ratio assessments could reflect an amelioration of the cardiovascular risk profile linked to hyperleptinaemia in ageing men with T2D.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 58 publications
5
21
0
Order By: Relevance
“…It remains unclear which method would fit the natural relations most optimally. Sex hormones may affect leptin concentrations, which has been suggested in studies on exogenous sex hormone administration in transgender persons [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…It remains unclear which method would fit the natural relations most optimally. Sex hormones may affect leptin concentrations, which has been suggested in studies on exogenous sex hormone administration in transgender persons [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Visceral adipose tissue is more strongly linked to insulin resistance than subcutaneous adipose tissue is. Though various RCTs have consistently proved that TRT can reduce total body fat mass, 77,8283,102103 its effects on regional fat redistribution are not consistently proven; some studies have shown a reduction in visceral adipose tissue 103104 whereas others have not. 79,102,105 These inconsistencies may be due to small sample sizes or imprecise methodology to quantify visceral adipose tissue like dual-energy X-ray absorptiometry or ultrasound.…”
Section: Areas Of Uncertaintymentioning
confidence: 99%
“…In one 24‐week study of 39 men with a bioavailable testosterone of 7.3 nmol/L (mean age 60 years, BMI 31 kg/m 2 , HOMA‐IR of 3.5 and HbA1c of 6.5%), testosterone gel treatment, despite expected changes in body composition (increase in lean mass by 1.9 kg and decrease in fat mass by 1.3 kg), had no effect on insulin sensitivity assessed by clamp, nor on HOMA‐IR or on HbA1c (Magnussen et al ., 2016). A subsequent magnetic resonance analysis of this cohort demonstrated no effect of testosterone treatment on metabolically adverse hepatic or visceral fat, but testosterone decreased the potentially insulin‐sensitizing adipokine adiponectin (Magnussen et al ., 2017). In contrast, a 24‐week clamp study enrolling 44 hypogonadal men (defined as free testosterone <225 pmol/L with a mean age 55 years, BMI 40 kg/m 2 , HOMA‐IR of 3.9, and HbA1c of 7.0%) while similarly demonstrating no change in visceral hepatic fat, found a 32% increase in insulin sensitivity with intramuscular testosterone treatment ( p = 0.03 for comparison with placebo), in association with upregulation of insulin signaling genes in adipose tissue (Dhindsa et al ., 2016).…”
Section: Metabolic Impact Of Testosterone Treatment In Clinical Trialsmentioning
confidence: 99%